Structural evolution of stretch deformed HDPE/RGO nanocomposites: An in-situ synchrotron SAXS and WAXD study. (20th October 2019) - Li, Yiguo; Duan, Tianchen; Yao, Guibin; Tang, Yujing; Miao, Weijun; Wang, Zongbao
Abstract: We have reported that the incorporation of reduced graphene oxide (RGO) can induce epitaxial crystallization of high density polyethylene (HDPE) on RGO surfaces and then enhance mechanical properties of HDPE/RGO nanocomposites, but the underline intensifying mechanism remains unclear. Herein, to further unveil the influence of epitaxial crystallization imposing on the improvement of mechanical properties, the structural evolution of HDPE/RGO nanocomposites during the stretching process is explored as a function of RGO content by in-situ synchrotron wide angle X-ray diffraction (WAXD) and small angle X-ray scattering (SAXS) techniques. It has shown that the introducing of RGO apparently retards the structural evolution in the tensile deformation and the hysteresis is accentuated dramatically with increasing RGO content. The epitaxial growth of HDPE upon RGO surfaces forms large sized crystals and the amount of epitaxial crystals enlarges with RGO content. The coupling of the remained existence of large sized crystals and the smaller density after stretching demonstrates that the interplay between RGO and large amount of epitaxial crystals can undergo the strong stress and thus hampers and delays the structure change and crystal fragmentation during the tensile deformation of HDPE/RGO nanocomposites. The present results not only makes clear that it is the epitaxial crystallization stemming from interfacial interaction between HDPE and RGO that plays the major role to delay the structural evolution and damage and thus lead to the enhancement of mechanical properties of HDPE/RGO nanocomposites, but reveal the underline stress-induced fragmentation-recrystallization mechanism for this tensile deformation.